2007
DOI: 10.1093/ageing/afl150
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 deficiency in the aged: a population-based study

Abstract: undiagnosed vitamin B12 deficiency is remarkably common in the aged, but no specific risk group for screening can be identified. Thus, biochemical screening of unselected aged population is justified. General practitioners play a key role in diagnosing early vitamin B12 deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
75
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 22 publications
8
75
3
4
Order By: Relevance
“…In this study, older aged individuals had significant lower hemoglobin level and such observations have been reported by previous studies [23]. We also found similar correlation with vitamin B12 like earlier studies [24]. It could be a mixed effect, as vitamin B12 is one of the important components in haemopoiesis.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, older aged individuals had significant lower hemoglobin level and such observations have been reported by previous studies [23]. We also found similar correlation with vitamin B12 like earlier studies [24]. It could be a mixed effect, as vitamin B12 is one of the important components in haemopoiesis.…”
Section: Discussionsupporting
confidence: 92%
“…Vitamin B12 is an essential cofactor and coenzyme mediating 2 enzymatic reactions. One involves the conversion of methylmalonyl-coenzyme A (CoA) to succinyl-CoA using adenosyl-Cbl (Ado-Cbl) as a cofactor; the other involves the synthesis of methionine from homocysteine using methyl-Cbl as a cofactor [1] . Impairment in the latter reaction leads to defects in DNA synthesis and a disruption in megaloblastic maturation pattern, as well as the defective productions of choline and choline containing phospholipids that are believed to be of primary importance in explaining the pathophysiological aspects of vitamin B12 and folate deficiencies [13,14] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating evidences have shown that vitamin B12 deficiency is a relatively common disease, whose prevalence increases with aging [1,2] . Vitamin B12 deficiency is a worldwide problem, and some researchers regard vitamin B12 as a critical vitamin in old population [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin B 12 levels decreases with age [1], which means that deficiency risk increases in parallel with age [2][3][4]. Therefore, subclinical deficiency is quite more prevalent in the elderly.…”
Section: Introductionmentioning
confidence: 99%